Threat vs. Threat: Attention to Fear-Related Animals and Threatening Faces - Berdica, Elisa; Gerdes, Antje B. M.; Bublatzky, Florian; White, Andrew J.; Alpers, Georg W. (Frontiers in Psychology, 2018)
It is generally thought to be adaptive that fear relevant stimuli in the environment can capture and hold our attention; and in psychopathology attentional allocation is thought to be cue-specific. Such hypervigilance toward threatening cues or difficulty to disengage attention from threat has been demonstrated for a variety of stimuli, for example, toward evolutionary prepared animals or toward socially relevant facial expressions. Usually, specific stimuli have been examined in individuals with particular fears (e.g., animals in animal fearful and faces in socially fearful participants). However, different kinds of stimuli are rarely examined in one study. Thus, it is unknown how different categories of threatening stimuli compete for attention and how specific kinds of fears modulate these attentional processes. In this study, we used a free viewing paradigm: pairs of pictures with threat-related content (spiders or angry faces) or neutral content (butterflies or neutral faces) were presented side by side (i.e., spiders and angry faces, angry and neutral faces, spiders and butterflies, butterflies and neutral faces). Eye-movements were recorded while spider fearful, socially anxious, or non-anxious participants viewed the picture pairs. Results generally replicate the finding that unpleasant pictures more effectively capture attention in the beginning of a trial compared to neutral pictures. This effect was more pronounced in spider fearful participants: the higher the fear the quicker they were in looking at spiders. This was not the case for high socially anxious participants and pictures of angry faces. Interestingly, when presented next to each other, there was no preference in initial orientation for either spiders or angry faces. However, neutral faces were looked at more quickly than butterflies. Regarding sustained attention, we found no general preference for unpleasant pictures compared to neutral pictures.